2003
DOI: 10.2355/isijinternational.43.245
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Grain Boundary Structure and Grain Growth in Bulk Silicon-Iron.

Abstract: Grain boundary shapes and grain growth in bulk 2.61 wt% silicon-iron have been studied by heat-treating at temperatures between 700 and 1 200°C. Initial microstructure with fairly uniform fine grains has been obtained by recrystallization at 800°C for 5 min after deformation. When subsequently heat-treated at 700 and 800°C, a fraction of the grain boundaries have hill-and-valley shapes with several facet planes or kinks. Some of these facet boundary segments are expected to be singular. Abnormal grain growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
(106 reference statements)
1
3
0
Order By: Relevance
“…In silver, the abnormal grain growth occurred during anneals at low temperatures (700, 600 and 500°C, when a certain portion of GBs was faceted), and at high temperatures (920 and 800°C when all GBs were rough or non-faceted), the normal grain growth took place [176]. Similar effect of temperature and resulting GB facetingroughening has been observed in stainless steel [177][178][179] and in Fe-Si alloys [180]. Thus, when commercial 316L stainless steel specimens are heat treated in a single-phase state at 1100°C, abnormal grain growth occurs, and some GBs are faceted with hill-and-valley structures in TEM.…”
Section: Faceting-roughening Of Low-angle Grain Boundariessupporting
confidence: 56%
See 1 more Smart Citation
“…In silver, the abnormal grain growth occurred during anneals at low temperatures (700, 600 and 500°C, when a certain portion of GBs was faceted), and at high temperatures (920 and 800°C when all GBs were rough or non-faceted), the normal grain growth took place [176]. Similar effect of temperature and resulting GB facetingroughening has been observed in stainless steel [177][178][179] and in Fe-Si alloys [180]. Thus, when commercial 316L stainless steel specimens are heat treated in a single-phase state at 1100°C, abnormal grain growth occurs, and some GBs are faceted with hill-and-valley structures in TEM.…”
Section: Faceting-roughening Of Low-angle Grain Boundariessupporting
confidence: 56%
“…If all GBs have a rough structure, then a nearly isotropic normal grain growth occurs. The abnormal grain growth is observed to occur when all or a fraction of the GBs are faceted [126,160,[173][174][175][176][177][178][179][180][181][182][183][184]. Below follows the detailed discussion of the works [126,160,[173][174][175][176][177][178][179][180][181][182][183][184].…”
Section: Faceting-roughening Of Low-angle Grain Boundariesmentioning
confidence: 99%
“…G RAIN boundaries of hill-and-valley (h&v) shapes with alternating parallel segments or kinked shapes (as observed at cross sections) with flat or curved segments intersecting at joints have been observed in many metals (Au, [1][2][3] Ni, 4,5 Al, 2,6,7 Ag, 8 -10 Cu, 11 Zn, 12,13 316L stainless steel, 14,15 a Ni-base superalloy, 16 Si-Fe, [17][18][19] Cu-Bi, 20 -22 and Fe-Te 23,24 ) and some oxides (MgO, 25 MgO⅐2Al 2 O 3 , 26 NiO, 27 Al 2 O 3 , 28 -34 and BaTiO 3 35-39 ) with both special and general misorientation angles between the grains. Some flat segments of the h&v boundaries were parallel to low-index planes of one or both of the grain pairs 1,3,28,32,34 -39 and likely to be singular corresponding to cusps in the polar plot of the boundary energy ␥ against the normal direction.…”
Section: Introductionmentioning
confidence: 99%
“…In polycrystalline Au, Ichinose and Ishida 8) reported that about 30% of the grain boundaries observed were low index grain boundaries but the macroscopic shapes of the boundaries were not described. In Ni, 17) 316L stainless steel, 18) a Ni-base superalloy, 19) Si-iron 20) and alumina, 16) grain boundaries with hill-and-valley (h&v) shapes were observed. Although the segments of these boundaries were likely to be singular, the orientations of their boundary planes were not determined.…”
Section: Introductionmentioning
confidence: 99%